MATLAB/Simulink based simulations of KY converter for PV panels powered LED lighting system - Sureshkumaar, G.; Kannan, Nithiyananthan; Thomas, Sunil (International Journal of Power Electronics and Drive Systems (IJPEDS), 2019)
The main objective of this research work is to develop KY conveter topology for renewable energy sources.Solar energy is the readily available and is the cheapest form of energy. It is non-polluting and environment friendly. The development of high static gain DC-DC converters is an important research area due to the crescent demand of this technology for several applications supplied by low DC output voltage power sources. It is used to provide the uninterruptable power supply and battery powered to the system. So here, step-up DC-DC converters based on the KY converter are proposed for LED lighting systems. The proposed topologies present high voltages and high efficiency for low input voltage and high output voltage applications. The simulation results of the proposed topology have been presented using MATLAB/SIMULINK software.